2021
DOI: 10.3390/sports9020017
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Practice and Nitrogen Balance in Elite Japanese Swimmers during a Training Camp

Abstract: The protein requirement in athletes increases as a result of exercise-induced changes in protein metabolism. In addition, the frequency, quantity, and quality (i.e., leucine content) of the protein intake modulates the protein metabolism. Thus, this study aimed to investigate whether nutritional practice (particularly, protein and amino acid intake at each eating occasion) meets the protein needs required to achieve zero nitrogen balance in elite swimmers during a training camp. Eight elite swimmers (age 21.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Regardless, the researcher also confirmed a significant and complex relationship between body composition status and sprint performance for both sexes [ 1 ]. Finally, a recent study on six elite-level female swimmers (age 21 years) from Japanese members of the national team or qualified in internal qualifications to participate in the preparation of their national training camp showed that their mean BH was 169.2 cm, BM was 60.6 kg, BMI was 21.2 kg/m 2 , and BF % was 17.7% (measured by bioimpedance) [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless, the researcher also confirmed a significant and complex relationship between body composition status and sprint performance for both sexes [ 1 ]. Finally, a recent study on six elite-level female swimmers (age 21 years) from Japanese members of the national team or qualified in internal qualifications to participate in the preparation of their national training camp showed that their mean BH was 169.2 cm, BM was 60.6 kg, BMI was 21.2 kg/m 2 , and BF % was 17.7% (measured by bioimpedance) [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, the researchers acknowledge that the energy needs depend on several factors, including type of swim stroke, body mass of the athlete, duration of the activity, and seasonality (training vs. competing) [ 4 ]. In the abovementioned recent study on six female members of the Japanese national swim team, the researchers included both sexes (also two males); therefore, these data for the preparation phase (i.e., day 1 to day 3) showed high energy intake (3889 kcal/d to 4447 kcal/d), 26–28% of energy from fat, 53–56% of energy from carbohydrates, and 17–18% of energy from protein [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lack of physical fitness and unbalanced nutritional status can interfere with a swimmer's development and growth [12]. Moreover, body movement when swimming requires energy [13], which comes from foods that contain sufficient nutrients [14].…”
Section: Introductionmentioning
confidence: 99%